2011
DOI: 10.1007/s10522-011-9353-4
|View full text |Cite
|
Sign up to set email alerts
|

B cell immunosenescence: different features of naive and memory B cells in elderly

Abstract: Elderly people show a reduced protection against new infections and a decreased response to vaccines as a consequence of impairment of both cellular and humoral immunity. In this paper we have studied memory/naïve B cells in the elderly, evaluating surface immunoglobulin expression, production of the pro-and anti-inflammatory cytokines, tumor necrosis factor (TNF)-a and interleukin (IL)-10, and presence of somatic hypermutation, focusing on the IgG ? IgD -CD27 -double negative (DN) B cells that are expanded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 47 publications
8
58
0
2
Order By: Relevance
“…We have confirmed data from the literature demonstrating impairment decrease of IgM B lymphocytes in the elderly (Shi et al 2005;Buffa et al 2011). On the contrary, a further evaluation of CO B cell populations revealed that the percentage of these cells are not reduced to the same extent as their age-matched controls and remain more similar to that observed in young people.…”
Section: Cd24supporting
confidence: 90%
See 3 more Smart Citations
“…We have confirmed data from the literature demonstrating impairment decrease of IgM B lymphocytes in the elderly (Shi et al 2005;Buffa et al 2011). On the contrary, a further evaluation of CO B cell populations revealed that the percentage of these cells are not reduced to the same extent as their age-matched controls and remain more similar to that observed in young people.…”
Section: Cd24supporting
confidence: 90%
“…5a). A comparison between our subjects confirmed (Shi et al 2005;Buffa et al 2011) a different distribution of B cells identified on the basis of these markers between young and old donors and revealed that CO possess a more "youthfully" distributed immune profile compared with age-matched controls. Indeed, the percentage of IgM + CD27…”
Section: Cd27supporting
confidence: 76%
See 2 more Smart Citations
“…For this reason the deep knowledge of B cell subsets and functions provides crucial information on immune assessment. Moreover B lymphocytes, due to their ability to present antigen to T lymphocytes, produce cytokines and synthesize granzymes, are now recognized as eclectic and essential cells for an exhaustive immune response (Blair et al, 2010;Bouaziz et al, 2010;Buffa et al, 2011;Hagn et al, 2009Mauri, 2010;Vitale et al, 2010). The different B cell subsets have been identified using many cellular markers by which many functional subsets, as transitional, naïve, memory and plasmablasts may be recognized.…”
Section: Introductionmentioning
confidence: 99%